(untitled) (Integral Research, 2025)
The growth of information and communication technology (ICT) has lent some transformation in the educational system through the application of modern equipment and blending same with the conventional classroom interaction between teachers and students/learners thereby introducing the blended learning system of instructional delivery. It has given rise to e-instructional methods that is both synchronous and asynchronous like blended learning. While there is growing research on the benefits of blended learning across various disciplines, there is a gap in understanding how it specifically influences intrinsic motivation within Political Science education. This study aims to fill that gap by examining students’ perceptions of blended learning and its effect on intrinsic motivation to learn among Undergraduate students. This paper addressed the review in threefold objective by exploring the conceptualization of blended learning, political education, the role of intrinsic motivation in learning, as motivation is an all-inclusive trait in human behaviour, and provided insights into how blended learning interjected to improve educational outcomes.